2015
DOI: 10.1007/s13202-015-0193-7
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory investigation of the factors impact on bubble size, pore blocking and enhanced oil recovery with aqueous Colloidal Gas Aphron

Abstract: Colloidal Gas Aphron as a mobility control in enhanced oil recovery is becoming attractive; it is also designed to block porous media with micro-bubbles. In this paper, the effects of surfactant concentration, polymer concentration, temperature and salinity on the bubble size of the Colloidal Gas Aphron were studied. Effects of injection rates, Colloidal Gas Aphron fluid composition, heterogeneity of reservoir on the resistance to the flow of Colloidal Gas Aphron fluid through porous media were investigated. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, an increasing number of studies have found that CGA microbubbles improve oil recovery. Shi [31] highlighted an increase of 26.8% oil recovery by microbubble injection in tertiary conditions. Experiments on microbubbles under secondary recovery core flooding in 2015 by Akai [32] proposed an increase of 13% of oil recovery compared with normal CO 2 injection.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, an increasing number of studies have found that CGA microbubbles improve oil recovery. Shi [31] highlighted an increase of 26.8% oil recovery by microbubble injection in tertiary conditions. Experiments on microbubbles under secondary recovery core flooding in 2015 by Akai [32] proposed an increase of 13% of oil recovery compared with normal CO 2 injection.…”
Section: Introductionmentioning
confidence: 98%
“…Unfortunately, these foams tend to become unstable in high-temperature, high-pressure environments, and this lack of stability is a challenge with regard to EOR applications [7]. Recently, microbubbles (defined as having sizes of 10 to 100 μm) have become of interest as a means of removing contaminants from aqueous solutions [8,9], as components of oil well-drilling fluids [10][11][12][13][14] and also with regard to EOR [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is explained in Figure by monitoring the SDBS concentration within the effluent water. Although unfavorable for this study, the literature reports that the heteroaggregation of Al-NPs could be beneficial for a pore blocking agent study in heterogeneous reservoirs …”
Section: Resultsmentioning
confidence: 99%
“…Although unfavorable for this study, the literature reports that the heteroaggregation of Al-NPs could be beneficial for a pore blocking agent study in heterogeneous reservoirs. 38 3.2.2. Formation Damage.…”
Section: Evaluation Of Oil Recoverymentioning
confidence: 99%